(untitled) - J C Sharma (Hà Nội, 1992)
The book provides basic information about the Cham temples. A slightly detailed chapter on the history of Champa has beenincluded to acquaint the readers with events, circumstances and conditions prevailing during the periods in which temples were constructed
Keywords: temple of champa (central vietnam),temples - vietnam